The Efektifitas Arang Aktif Terhadap Peningkatan Kualitas Air Tanah dengan Metode Multi Soil Layering (MSL) - arief yandra; FITRI MAIRIZKI (JURNAL KATALISATOR, 2021)
Ground water pollution can be caused by various kinds of wastes and the results of human activities. Ground water containing COD, BOD and other harmful substances in high concentrations must pass through a treatment before use. Activated carbon is free carbon with an internal surface that has good absorption. One alternative to wastewater and groundwater treatment systems that is economical, does not require a large area and is easy to operate is the Multi Soil Layering (MSL) system. This study aims to determine the effectiveness of activated charcoal sources in reducing COD, BOD, heavy metal content and increasing groundwater pH. Sampling using random sampling technique. The MSL system uses a variety of activated charcoal sources, namely coconut shells, rice husks and sawdust. The results showed that the source of activated charcoal which gave the most effective increase in pH was rice husk (53.57%). In other hand, the sources of activated charcoal that decreased COD, BOD, Hg, Pb, and Fe were sawdust (31.16%), rice husks (73.16%), coconut shells (70.75%), sawdust (26.74%), sawdust (46.94%), respectively. The best source of activated charcoal in reducing pollutant content in groundwater is sawdust.